Strategi Diversifikasi Produk Sebagai Upaya Meningkatkan Penjualan Susu Sapi Rembangan - Landy, Savero; Rabbana, Muchsin Auda; Khasanah, Elisa Uswatun; Aji, Joni Murti Mulyo; Prasetyo, Atwindarsyah Aries (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This community service is part of a professional internship program that focuses on product diversification strategies as an effort to increase sales, improve competitiveness, and the sustainability of the dairy business at Rembangan Dairy Farm, Jember. The primary issues addressed include limited variety in processed milk products and suboptimal marketing strategies, which affect product quality consistency and market expansion. The objectives of this initiative are to analyze the effectiveness of product diversification strategies, identify internal and external factors influencing these strategies, and formulate development recommendations by designing a more adaptive business model using the Business Model Canvas (BMC). The methods employed include direct observation, interviews with stakeholders, and hands-on participation in operational activities such as livestock care, milk processing, and interviews during a 45-day internship at the UPT Pembibitan Ternak dan Hijauan Pakan Ternak Rembangan. The results demonstrate that product diversification, including flavored milk, milk pudding, and cheesecuit, successfully increased consumer appeal and product value. The BMC analysis mapped nine key business elements and provided a foundation for more structured strategic recommendations. This program offers strategic recommendations for the sustainable development of the dairy agroindustry.